2016
DOI: 10.1111/joms.12198
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Environmental Entrepreneurship: Identity Coupling, Venture Goals, and Stakeholder Incentives

Abstract: On the basis of a qualitative study of 25 renewable energy firms, we theorize why and how individuals engage in environmental entrepreneurship, inductively defined as: the use of both commercial and ecological logics to address environmental degradation through the creation of financially profitable organizations, products, services, and markets. Our findings suggest that environmental entrepreneurs: (1) are motivated by identities based in both commercial and ecological logics, (2) prioritize commercial and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
238
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(253 citation statements)
references
References 115 publications
(216 reference statements)
7
238
1
7
Order By: Relevance
“…Besides, the directly proportional relationship between uncertainty and innovation opportunities must be analyzed by performing empirical tests on social entrepreneurship initiatives in the field of sustainable energies [57] and by analyzing how ecologically sustainable entrepreneurs and their companies influences communities and society [30], since social and ecological factors can be a source of business opportunities [44]. This document also provides an exhaustive analysis of the selected works, showing possible gaps and opportunities for new researches on sustainable entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the directly proportional relationship between uncertainty and innovation opportunities must be analyzed by performing empirical tests on social entrepreneurship initiatives in the field of sustainable energies [57] and by analyzing how ecologically sustainable entrepreneurs and their companies influences communities and society [30], since social and ecological factors can be a source of business opportunities [44]. This document also provides an exhaustive analysis of the selected works, showing possible gaps and opportunities for new researches on sustainable entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…Also, [56] claims that translating a sustainability message into a tangible product involves the support of three techniques: preservation, transformation and adding novelty. Other authors [44] [57][58][59][60] refer to the key findings that the triple bottom line of ecological, social and economic goals is integrated sequentially, not simultaneously, that is to say, sustainable entrepreneurs must: (1) be motivated by identities based on both commercial and ecological logics; (2) prioritize commercial and/or ecological goals; and (3) approach stakeholders in a broadly inclusive, exclusive, or co-created manner in order to acquire financial resources through crowdfunding, because sustainable entrepreneurs do not seem to be ready to respond to the challenges or to take any risks by investing in green business, but also that the government and educational institutions do not recognize their own role and the need of supporting the development of green entrepreneurship.…”
Section: Phase 2: Analysis Of the Literaturementioning
confidence: 99%
“…First, what the fields of social, environmental, 1 and sustainable entrepreneurship share is the drive of entrepreneurs to create value for others by identifying and seizing upon opportunities arising from problems in society that have been neglected or unsuccessfully addressed by public, private, or civil society organizations (Schaltegger and Wagner 2011;York et al 2016). In this context, value creation can be understood as an increase in the aggregate utility for society's members owing to entrepreneurial activity (Santos 2012).…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%
“…2 See, for an overview, Schaltegger and Wagner (2011) and Thompson et al (2011). Venkataraman 2010). They do so in a for-profit context that combines environmental and economic value creation (York et al 2016), with its disciplinary root being environmental economics (Thompson et al 2011). Sustainable entrepreneurs explicitly focus on a combination of social, environmental, and economic goals (Elkington 1997).…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%
“…At the frontier of such efforts, York et al (2016) found that "environmental entrepreneurs" are motivated by both commercial and ecological concepts and prioritize their development efforts based on the strength and linkages between these two concepts. Organizational theories also recognize a level of social responsibility, along with the creation of novel hybrid organizations (Battilana et al, 2012;Smith et al, 2013;Hockerts, 2015).…”
Section: The Private Sectormentioning
confidence: 99%